The Impact of Social Media on Student Learning - Kirti Kumari (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Social media has become an undeniable force in our lives, and its influence extends to the classroom. This research paper will explore the impact of social media on student learning, examining both its potential benefits and drawbacks. The paper will consider how social media can be used to enhance learning, such as by providing access to educational resources and fostering collaboration among students. However, it will also discuss the challenges posed by social media, such as distraction, cyberbullying, and the spread of misinformation. By analyzing relevant research and considering the perspectives of students, educators, and parents, this paper will aim to provide a comprehensive understanding of the complex relationship between social media and student learning.